Scaling data analysis with Apache Mahout - Drost, Isabel (O'Reilly Media, 2011)
"With growing amounts of digital data at the fingertips of software developers, the need for a scalable, easy to use framework is tremendous. This talk introduces Apache Mahout--a project with the goal of implementing scalable machine learning algorithms for the masses."--Resource description page.